The Genesis of Systemic Conflicts in the Period of the USSR Collapse and State Formation in the Post-Soviet Period - Ayvazyan, Vardan (Bulletin of Yerevan University C: Jurisprudence, 2023)
The object of the study is the genesis of systemic conflicts in the paradigm of the phenomenology of statehood, with its inherent methodological and methodical approaches to the mechanisms of formation and building of the state task, which presupposes the systems of interacting institutions that determine the structure of public administration.The subject of the study is the main trends of statehood formation in modern history, a systemic crisis of administration in the decline period, and the actual trajectory and mechanics of statehood formation in the post-Soviet space and in the world after the collapse of the USSR. Special attention is paid to the analysis of key causes of the emergence of systemic conflicts as a result of differences in content, understanding, and installation of the structure of state building on an operational level without a qualitative legal metric of legitimacy of state-formation. The genesis of systemic conflicts of constitutional and legal regulation in the conditions of the growing scale of global integration, as well as the critical need for an effective supranational level of legal regulation within the framework of a systemically full-fledged international law.The study concludes that due to systemic conflicts, ensuring common understanding, interpretation and application of the guiding principle of the Rule of Law becomes ambiguous and makes the formation of a common unified global legal space impossible. As a result, as an objective consequence, integration processes, in the absence of a systematically organized legal discipline, go into the mode of "self-determination" where the principle Rule of Law based on a system of legal norms on the long term basis, is replaced with a conventional system of situational agreements oriented on the rules of the short-term basis of the current conjecture.
Keywords: Genesis; legal genesis; systemic conflicts; sin; Constitution; constitutional regulation; the Rule of Law; the USSR; world order; civilization